(untitled) (Research, Society and Development, 2021)
The main requirement for the insertion of dental implants is a good bone and gum condition and guided bone regeneration (GBR) combines grafts and membranes to increase such parameters in tissue deficiencies and thus achieve treatment success. This clinical case reports the oral rehabilitation of the anterosuperior area by the association of bone graft, autologous membrane and implantodontic therapy. Female patient, 45 years old, normosystemic, reported aesthetic complaint and implant mobility in the maxilla. Upon clinical and radiographic examination, an implant was diagnosed in the region of tooth 11 with unfavorable esthetics, mobility, inadequate prosthesis and bone loss, and tooth 22 with suppuration, fracture line and periapical radiolucency. The treatment consisted of removal of the implant and tooth 22, with immediate GBR using filling with Bio-Oss® and liquid leukocyte- and platelet-rich fibrin (L-PRF) and coating with L-PRF membrane. After 7 months, the second GBR was performed with the installation of 2 dental implants. After 6 months, healers were placed and 20 days after the adaptation of the provisional implant-supported single prostheses. There was a good gain in thickness and mucogingival limit, bone dimensions in height and thickness, and the case continues to be followed up until the final prosthesis is completed. This case suggests that sticky bone and L-PRF membrane can contribute to multiple GBR in the anterior maxillary region, favoring bone gain and osseointegration.